Still agreeing to disagree: international security and constructive ambiguity - Byers, Michael (Journal on the use of force and international law, 2021)
This article - which updates and builds on an earlier piece published in Global Governance in 2004 - concerns the deliberate use of redundancies, contradictions, imprecisions and other ambiguities in UN Security Council resolutions on the use of force, centrally including Resolution 1441 on Iraq, Resolution 1973 on Libya, and Resolution 2249 on Syria and Iraq. 'Constructive ambiguity', a term generally attributed to former US Secretary of State Henry Kissinger, is employed in many areas of international law. This article identifies five different forms of constructive ambiguity found in Security Council resolutions and suggests reasons for why this drafting strategy is used. It concludes by considering the implications of this research for our understanding of the role of international law in international peace and security. It finds that ambiguity, deployed deliberately and strategically, is not the 'design weakness' that some scholars consider it to be.